(3GdUfGYI GdUZjQIs - (3LGdjfhSs
(3ChdgG (B:s
(3EfeG GdeSGdc ai GdJYdje MSH QCi HYV GdfGS NeSI , CMOgG , GdPi jLQi GdCeQ ajg Ydi WQjb GdWH hGdYcS s
(3BNQgG (B:s
(3hHGdTQGH GdehGab , eKd GdNeQI GddWjaI GdQGYGjI , GdJi df JYJb hGdQjGVI GdeYJOdI , eKd GdeTi GdeYJOd , hGdMeGe GdQchH s
(3ghGdcJGH GdKGfi ef LhGeY GdcJH GdSJI YTQ dLGdjfhSs
(3GdJi cGfJ JbQC Ydi GdeYdejf HGdGScfOQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B205 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B123 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjG UhajG (B(3588(2)) s
Keywords: (3GdWHs